Berberine’s Therapeutic Prospects in Parkinson’s Disease: A Spotlight on Cholesterol Regulation for Cognitive Improvement - Lakshmi Narayanan, T; Thekkekkara, Dithu; Chattu, Manasa Renu Srivalli; Babu, Amrita; Kondaveeti, Sreenivasulu Naidu; Meheroonisha, SK.; Sai, Thummuru Ekshita (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Cholesterol synthesized in astrocytes of the cerebrum plays a pivotal role in regulating hippocampal neurogenesis and cognitive function. Dysregulation of cholesterol metabolism has emerged as a key contributor to the pathogenesis of Parkinson’s disease. Elevated cholesterol levels in the brain are associated with increased oxidative stress and subsequent neurodegeneration of hippocampal pyramidal neurons, culminating in cognitive impairment. Berberine, an isoquinoline alkaloid has the potential to modulate cholesterol synthesis through HMG-CoA inhibition. Aim This study aims to elucidate the therapeutic potential of berberine in mitigating cognitive impairment in Parkinson’s disease by conferring protection to hippocampal pyramidal neurons through regulating cholesterol homeostasis. Materials and Methods Parkinson’s disease was induced in male Sprague Dawley rats through the administration of rotenone (intraperitoneal, 2.5 mg/kg) for 42 days, followed by treatment with the berberine (oral administration, 10 mg/kg and 40 mg/kg) for 21 days. The efficacy of berberine was assessed through evaluations encompassing cognitive function, motor coordination, locomotor activity, biochemical analyses, and histopathological examinations. Results Our findings revealed that berberine, administered intraperitoneally at a dose of 40 mg/kg, effectively ameliorated the symptoms associated with Parkinson’s disease. This amelioration was concomitant with reduced cholesterol levels within the brain and an elevation in dopamine levels when compared to the disease-induced control group. The hippocampus of the berberine-treated group showed preserved pyramidal neurons and a decrease in macrophage and microglial infiltration, which were strongly correlated with the reported improvement in cognitive performance. Conclusion Our study underscores the potential therapeutic utility of berberine in mitigating cognitive impairment in Parkinson’s disease. The findings presented here provide valuable insight into the mechanisms underlying the beneficial effects of berberine in Parkinson’s disease and suggest its promise as a therapeutic agent in managing cognitive deficits associated with this neurodegenerative disorder through regulating cholesterol homeostasis.
Keywords: Parkinson’s Disease; Cognitive impairment; Dopamine; Cholesterol; Alpha-synuclein; Berberine